Larvicidal Activity of Red Betel (Piper Crocatum, L) Leaf Chloroform Extract Granule against Aedes Aegypti Larvae - Ikhsanudin, Azis; Tri Hastuti, Haadiyatul; Lolita, Lolita; Tajjudin, Saiful Nizam (Clinical and Pharmaceutical Sciences Journal, 2025)
Dengue fever is a disease caused by the bite of the Aedes aegypti mosquito. The development of natural larvicides needs to be done to reduce the risk of resistance and ensure environmental safety due to the use of chemical larvicides. Plants that have the potential as larvicides include red betel leaf, which contains alkaloids, flavonoids, tannins, and saponins. This study aims to determine the larvicidal activity of red betel leaf chloroform extract granules with LC50 and LC90 parameters against Aedes aegypti larvae. This study used a post-test control group design, where the chloroform maceration method was used in its extraction. The extract obtained was subjected to qualitative phytochemical identification and formulated into granules and tested for physical properties, namely: water content, flowability, and dispersion time and larvicidal activity test using a post-test control group design where the test group was divided into six groups, namely positive control (Abate®), negative control (placebo), treatment with extract concentrations of 0.18%; 0.24% and 0.48%. The results of the phytochemical test showed that the extract contained alkaloids, flavonoids, tannins, and saponins, while the granule test showed a water content of 3.02%, a flow rate of 2.07 g/second, and a dispersion time of 2.31 minutes. The granule concentration of 0.48% had a larvicidal activity of 98.67%, significantly different from placebo (p<0.05) and not significantly different from Abate (p>0.05). In conclusion, the chloroform extract granules of red betel leaves have larvicidal activity with an LC50 of 0.276% and an LC90 of 0.381% against Aedes aegypti larvae. Keywords: Aedes agypti, extract, granule, larvacidered betel